Role of Accountability Management in Activity of Industrial Enterprises - Babich, Oksana V.; Mityuchenko, Lyudmila S. (International Review of Management and Marketing, 2016)
The paper has conducted the analysis of the mechanism of accountability management at industrial enterprises. The paper has also revealed the main problems solved with the use of accounting management. It has analyzed the main programs demanding the formation in the conditions of the accounting approach realization to management over industrial enterprises at the present stage of the development of economic relations. Analysis of the state of the Russian industry demonstrates its crisis that outdated paradigm of management that the solvency of the budget of consumers, the lack of money and investment, high wear of equipment, difficulties with the sale of goods, imperfection of normative-legal base, lack of raw materials and fuel, as well as other reasons are not allowed to go. Keywords: accountability management, purpose-oriented program, structural divisions, industrial enterprise, tree of objectives JEL Classifications: L30, L53, M20